2009
DOI: 10.1103/physrevb.79.165110
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced structural distortion ofTbMnO3: A combined x-ray diffraction and x-ray absorption spectroscopy study

Abstract: The variation of electronic states and structural distortion in highly compressed multiferroic TbMnO 3 was probed by x-ray diffraction ͑XRD͒ and x-ray absorption spectroscopy ͑XAS͒ using synchrotron radiation. Refined XRD data enabled observation of a reduced local Jahn-Teller ͑JT͒ distortion of Mn sites within MnO 6 octahedra in TbMnO 3 with increasing hydrostatic pressure. A progressively increasing intensity of the white line in Mn K-edge x-ray absorption spectra of TbMnO 3 was detected with increasing pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…Ultimately, for DyMnO 3 , the nearly isotropic compression suggests that the Jahn-Teller distortion hardly changes. This is in good qualitative agreement with the (limited) data on Mn-O2 bond lengths measured by Rietveld refinements for LaMnO 3 , TbMnO 3 , DyMnO 3 , and GdMnO 3 [5,12,13,15].…”
Section: B Jahn-teller Distortion: Spontaneous Strain and Raman Specsupporting
confidence: 78%
See 1 more Smart Citation
“…Ultimately, for DyMnO 3 , the nearly isotropic compression suggests that the Jahn-Teller distortion hardly changes. This is in good qualitative agreement with the (limited) data on Mn-O2 bond lengths measured by Rietveld refinements for LaMnO 3 , TbMnO 3 , DyMnO 3 , and GdMnO 3 [5,12,13,15].…”
Section: B Jahn-teller Distortion: Spontaneous Strain and Raman Specsupporting
confidence: 78%
“…In contrast, only a couple of works have been reported on other manganites. Combined x-ray diffraction and x-ray absorption spectroscopy studies on TbMnO 3 and DyMnO 3 showed a gradual decrease of the Jahn-Teller distortion and a bandwidth broadening, but could not clarify the presence of insulator-to-metal transition itself [12,13]. High-pressure Raman studies of TbMnO 3 and PrMnO 3 up to 10 GPa [14] were focused on the compression mechanisms as inferred from the pressure evolution of Raman wave numbers.…”
Section: Introductionmentioning
confidence: 99%
“…First, we optimized internal atomic parameters imposing the A-AFM spin configuration, whereas we took the experimental lattice parameters under pressure from ref. 24 (note that measurements have been done at room temperature). We also extracted additional sets of lattice parameters by linearly interpolating experimental values.…”
Section: Methodsmentioning
confidence: 99%
“…In RMnO 3 , it is well known that the lattice contraction by chemical pressure, that is, substitution of R site with smaller rare-earth, mainly causes the decrease of the Mn-OMn bond angles 9 . In contrast, the application of physical pressure shortens Mn-O bond lengths but increases the Mn-O-Mn bond angles 24 , so that both J 1 and J 2 are enhanced, therefore making the E-AFM spin configuration unusually stable in TbMnO 3 under pressure. …”
Section: Pressure Versus Temperature Phase Diagrammentioning
confidence: 99%
“…Structurally, CIS can be viewed as one of derivatives from binary CdTe through isovalent element substitution, and the tetrahedrally coordinated framework is inherited from the parent material. Accordingly, both compounds are composed of high symmetry ACh 4 tetrahedron units and obey the electron octet rule, where A is the cation element and Ch the chalcogen, while different symmetries might occur depending on the ordering of the cations [10]. To meet the desired TW production level in the future, however, CdTe and CIS photovoltaics technologies might run into sustainable problems mainly due to the relative scarcity of In and Te, as well as the toxicity of Cd.…”
mentioning
confidence: 99%